Sifat Fisika Tanah dan Produktivitas Kelapa Sawit (Elaeis Guineensis Jacq.) Di Lahan Gambut Pada Tinggi Muka Air Tanah Yang Berbeda - Wawan Wawan; Al Ichsan Amri; Afta Nurwanto Akbar (Jurnal Agroteknologi, 2019)
This study aims to determine soil physical properties and palm oil productivity in different of water levels (TMA) in peatland. This study conducted in palm oil plantation area in PT. Tabung Haji Indo Plantation Indragiri Hilir Regency, and Laboratory of Soil Science Faculty of Agriculture, University of Riau. This study was carried out started from July until October 2017 by using survey method. Sampling Location conducted by purposive sampling, and sampling point was determined by stratified random sampling. Analysed data used analyse of variance, followed by further test by Duncan’s new multiple range test level of 5%. Parameters observed in physical properties ware bulk density, porosity, water content of maximum occupied capacity, particles size distribution, and palm oil productivity. The result of this study showed that peatland with water levels (20-40) cm (TMA1) showed higher water content of maximum occupied capacity than water levels (>40-60) cm (TMA2), and >60 cm (TMA3). Peat soil with water level TMA2 owned bulk density, the particle size (≤63 µm) higher compared to TMA1 and TMA3. Peat soil with TMA3 showed higher porosity compared to TMA1 and TMA2. Peat soil TMA1 showed higher palm oil productivity compared to TMA2 and TMA3. Palm oil productivity TMA2 and TMA3 showed lower compared to TMA1 is caused by Ganoderma attack.